Amenity-Led Migration in Rural Australia: A New Driver of Local Demographic and Environmental Change? - Argent, N.; Tonts, M.; Jones, Roy; Holmes, J. (Co Published - Springer Science + Business Media and CSIRO Publishing, 2011)
There is growing acceptance that the fortunes of the non-metropolitan Australian ecumene are increasingly dependent on the interchanges of population, capital and ideas between cities and rural towns and regions. Yet we know relatively little about the push and pull forces drawing city residents into rural areas, or the medium- to long-term consequences of ex-urban in-migration for local land uses and the demographic and socio-economic composition of towns and regions. In this chapter, we critically investigate the relationships among rural amenity (as defined by a multivariate model which comprises the ‘amenity index ’) and in-migration trends across the rural ecumene of Western Australia, South Australia, Victoria and New South Wales for the 1991–1996 and 2001–2006 intercensal periods. Rural amenity is indeed an important influence on the location decision-making of ex-metropolitan migrants, but it is important to realise that counterurbanisation flows (i.e., people moving from cities to rural areas) comprise only a relatively small share of rural in-migration gains. In the high amenity communities in which these migrants are making their new homes, local demographic, socio-economic and land use structures are undergoing dramatic change, but not always along easily predicted lines. This situation poses clear policy challenges for those entrusted with the governance of high-amenity rural areas as they attempt to deal with, on the one hand, the grounded issues of settlement, land use and environmental management and, on the other, the different visions and aspirations of an increasingly diversified local population.